(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
In this work, we consider numerical modeling of localized surface plasmon resonances (LSPR) in silicon nanoparticles doped with rare-earth elements (Eu, Er, Yb). Literature data on the complex dielectric function ε(ω) for crystalline Si and the corresponding silicides (EuSi₂, ErSi₂, YbSi₂) were used to construct models of spherical nanoparticles, including core–shell configurations with a SiO₂ oxide shell. Using Python-based software (implementation of Mie theory), absorption and scattering spectra were calculated and the position of the LSPR peak was determined. The influence of nanoparticle radius (≈10–100 nm), doping concentration, and the refractive index of the surrounding medium on the position and width of the plasmon peak as well as on local field enhancement was investigated. Based on the analysis of the obtained dependences, recommendations are formulated for selecting Si–RE nanostructure parameters to tune the resonance within the required spectral range (visible or infrared) for sensing and photonic applications.